Elizabethkingia anophelis: An uncommon cause of hospital-acquired septic meningitis and a rare cause of community-acquired meningitis in children: A case series - Sarjana Shuchi; Shweta Satija; Manoj B Jais (Asian Journal of Medical Sciences)
Elizabethkingia is one among several new organisms which heve emerged as an important human pathogen in the past few decades. We present the first two cases of Elizabethkingia anophelis infection reported from our institution. The first case was of septic meningitis in a 10-day-old preterm neonate after 10 days of hospital stay and another case was of community-acquired meningitis in a 2-month-old infant. The organism was isolated from the cerebrospinal fluid of both the patients and the blood of only the neonate. E. anophelis is now being identified as the most prevalent species under the genus Elizabethkingia. Among the two cases, one was a health-care-associated infection and another was a community-acquired infection. Both cases improved after giving appropriate antibiotics. Hence, we should look for these kind of cases for early identification and to prevent mortality in patients by starting the right antibiotic.